PENERAPAN METODE PENEMUAN TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI LUAS PERMUKAAN DAN VOLUME BALOK - Purwatiningsi, Sri (Jurnal Elektronik Pendidikan Matematika Tadulako, 2013)
Abstract:The Objective of this research was to obtain the learning descripsion applying guided discovery learning method in effort to increase learning outcome on material of surface area and volume of cubein VIII SMP Negeri 12 Palu. This was a classroom action research refered to Kemmis and MC Taggart reseach design. Based on the research results, the learning applied guided discovery learning method can increase studentsâ learning outcome on the material of surface area and volume of cube namely: (1) orienting the students on the problem, (2) organizing the students in learning, (3) guiding individual and group insvestigation, (3) presenting activity result and (5) evaluating studentsâ learning achievenment.